Effects of repeated cigarette smoke extract exposure over one month on human bronchial epithelial organotypic culture - Shigeaki Ito; Kanae Ishimori; Shinkichi Ishikawa (Toxicology Reports, 2018)
Cigarette smoke is a known risk factor for inflammatory diseases in the respiratory tract, and inflammatory exacerbation is considered pivotal to the pathogenesis of these diseases. Here, we performed two repeated exposure studies in which we exposed human bronchial epithelial tissues in an organotypic culture model to cigarette smoke extract (CSE); the first study was conducted over a four-day period to determine the suitable dose range for the extended exposure period, and the second was a one-month exposure study to elucidate the exposure-by-exposure effects in bronchial tissues. We focused on matrix metalloproteinase (MMP)-9 and -1/3 and the inflammatory cytokines interleukin (IL)-8 and growth factor related oncogene to evaluate the transition into an inflammatory state. Even at CSE doses with no or low toxicity for a single exposure, the repetition of exposure induced cumulative effects on both the inflammatory responses, specifically the IL-8 and MMPs levels, and tissue morphology. Interestingly, untreated controls initially had relatively high baseline levels of these secreted proteins; these levels gradually declined, after which they showed periodic level changes, suggesting an acclimation period may be needed for this system. These results demonstrate the usability of this system for the elucidation of sub-chronic effects in vitro. Keywords: Cigarette smoke extract, Repeated exposure, Organotypic culture